Effective maintenance policy as a tool for sustaining housing stock in downturn economy - O.A. Adenuga,; M.B. Olufowobi,; A.A. Raheem, (Penerbit UKM, 2010)
The study considered how effective maintenance strategies could serve as a tool for sustaining housing delivery in periods of economic recession. It identified the causes of neglect of maintenance responsibilities in some selected government institutions, ministries, parastatals and public estates within Lagos metropolis and to develop adequate maintenance implementation strategies for these buildings. In achieving these objectives, opinions of (30) randomly sampled maintenance officers of selected government institutions, ministries, parastatals, and occupiers of selected public estates were collected using structured questionnaires and personal interviews. Data analysis indicated that lack of discernible maintenance culture in the country; lack of emphasis on training, retraining and continuing education on effective maintenance by establishment are the major reasons for neglect of maintenance responsibilities. The study also revealed that majority of the population studied provides budgets for maintenance operation but this was found to be inadequate. The study recommended proactive approaches to maintenance by providing guidelines for maintenance checklist operations on key building elements, frequencies for maintenance operations, and operatives required for effective implementation.